Mergers & Acquisitions in China - Devonshire-Ellis, Chris; Scott, Andy; Woollard, Sam (China briefing., 2011)
This guide takes a detailed look at all aspects of purchasing part or all of a business in China. Written specifically for businesses to understand all the nuances of China M&A, it details the complete regulatory processes involved as well as the differences that arise when handling M&A between private Chinese companies, Chinese State-Owned Enterprises, and Chinese Listed Corporations. It also deals with the acquisition of bankrupt assets and auction procedures. China Briefing's guides are leaders in their field, provide practical and pragmatic legal and tax information for foreign investors in the PRC and are of specific interest to all businessmen, lawyers, accountants, advisors and academics working in this field.